Dinamika Komunikasi Antar Budaya Mahasiswa Asrama IAHN Gde Pudja Mataram - ., Triwiyoso; Suardana, I Ketut Putu; Widaswara, Rieka Yulita (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2024)
This study highlights the dynamics of intercultural communication within the environment of IAHN Gde Pudja Mataram dormitory, which serves as a residence for students from diverse ethnic and cultural backgrounds. Located at Jl. Pancaka No. 7B Mataram, this dormitory is an integral part of the IAHN Gde Pudja Mataram campus, accommodating students from various regions of Indonesia, including Java, Bali, Maluku, and Lombok. The primary focus of the research is to identify, observe, and explore the dynamics of intercultural communication, the language proficiency of both students and faculty, and intercultural awareness in shaping harmonious and inclusive multicultural communication among dormitory residents. The research findings indicate that a high level of intercultural awareness among dormitory residents enables them to adapt their communication styles according to their respective cultural backgrounds, thereby reducing the risk of misunderstandings or miscommunication. Furthermore, this level of awareness also strengthens cooperation, tolerance, and harmony within the dormitory environment through activities such as communal work and collective prayers, creating a warm, inclusive, and safe atmosphere for all residents, both students and faculty alike. Observations of various activities conducted in IAHN Gde Pudja Mataram dormitory also illustrate the importance of this intercultural awareness in fostering harmonious and supportive relationships among dormitory residents. Thus, this research provides deep insights into how the dynamics of intercultural communication contribute to the formation of identity and social interaction within the rich cultural diversity context of Indonesia, as reflected in the IAHN Gde Pudja Mataram dormitory.